Investment climate, growth, and poverty - Kochendörfer-Lucius, Gudrun; Pleskovic, Boris (Berlin Workshop series, 2005)
"This volume presents papers from Berlin Workshop sessions on investment perspectives; securing property and contractual rights; the role of financial markets in spurring investment; regulation, governance, and corruption; selective interventions; and reforming the investment climate."--Jacket